(untitled) (International Conference on Educational Discoveries and Humanities, 2025)
Global cooperation has become an integral part of the social, economic, political and cultural processes that are taking place worldwide today. Countries, organizations and individuals in different parts of the world seek to increase solidarity in many areas in order to strengthen their ties. The role of language and communication in this process is incomparable. Language is not only a tool for people to understand each other, it also acts as an intercultural bridge, brings people closer and is an important measure in the effective conduct of global dialogue.